2023
DOI: 10.2196/45887
|View full text |Cite
|
Sign up to set email alerts
|

An Online Acceptance and Mindfulness Intervention for Chronic Pain in Veterans: Development and Protocol for a Pilot Feasibility Randomized Controlled Trial

Abstract: Background In the veteran community, chronic pain is particularly prevalent and often debilitating. Until recently, veterans with chronic pain were offered primarily pharmacological intervention options, which rarely suffice and can also have negative health consequences. To better address chronic pain in veterans, the Veterans Health Administration has invested in novel, nonpharmacological behavior interventions that target both pain management and chronic pain–related functional issues. One appro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Multimedia Appendix 4 [ 10 , 11 , 26 - 57 ] presents a summary of the studies included in this review. The characteristics of the included studies are presented in detail in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Multimedia Appendix 4 [ 10 , 11 , 26 - 57 ] presents a summary of the studies included in this review. The characteristics of the included studies are presented in detail in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies that reported a study design, mixed method studies (8/36, 22%) [ 10 , 28 , 39 - 44 ] and pilot studies (8/36, 22%) [ 31 , 34 , 38 , 45 - 48 ] were the most commonly used study designs, followed by qualitative studies (6/36, 17%) [ 11 , 26 , 35 , 49 - 51 ], randomized controlled trials (5/36, 14%) [ 32 , 37 , 52 - 54 ], ongoing trials (4/36, 11%) [ 33 , 55 - 57 ], quasiexperimental designs (2/36, 6%) [ 30 ], longitudinal study (1/36, 3%) [ 29 ], single-group nonrandomized trial (1/36, 3%) [ 36 ], and pre- and posttest design (1/36, 3%) [ 27 ]. Of the 36 studies, 30 (83%) were conducted on patients (15/36, 42%) [ 10 , 26 , 32 , 34 - 37 , 40 , 42 , 47 , 52 , 54 - 57 ] or healthy individuals (15/36, 42%) [ 11 , 27 , 29 - 31 , 44 - 46 , 48 - 51 , 53 ] and 6 (17%) [ 28 , 33 , 38 , 39 , 41 , 43 ] on stakeholders such as homecare providers or experts. The mean age of the target population across studies was >40 years, except for 19% (7/36) of the studies [ 30 , 33 , 35 , 47 , 53 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations